2003
DOI: 10.1159/000072546
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Polymyxin B-Immobilized Fiber Hemoperfusion on Amino Acid Imbalance in Septic Encephalopathy

Abstract: Background: Septic encephalopathy is a common term denoting the signs of progressing central nervous system dysfunction in septic patients. Metabolic alterations including amino acid imbalance are involved in the pathogenesis of septic encephalopathy. The aim of the present study was to determine whether the ratio of branched-chain amino acids to aromatic amino acids is altered in patients with septic encephalopathy and whether polymyxin B-immobilized fiber (PMX-F) hemoperfusion affects this balance. Methods: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…Terborg et al (11) have pointed out that vasomotor dysfunction which was regarded as the main cause of sepsis-associated encephalopathy, often leads to dysregulation of cerebral blood flow and can directly affect brain function and cerebral blood circulation. Studies have shown that patients with sepsis have relatively high levels of aromatic amino acids in plasma, which can easily lead to the production of pseudo-neurotransmitters, affect neuronal function, and cause symptoms and signs of various neurological impairments including disturbance of consciousness (12,13). Sharshar et al (14) performed pathological examination on the brain tissue of patients who died of sepsis and found that the incidence of microabscess was high and microabscess may be one of the causes of sepsis-associated encephalopathy.…”
Section: Discussionmentioning
confidence: 99%
“…Terborg et al (11) have pointed out that vasomotor dysfunction which was regarded as the main cause of sepsis-associated encephalopathy, often leads to dysregulation of cerebral blood flow and can directly affect brain function and cerebral blood circulation. Studies have shown that patients with sepsis have relatively high levels of aromatic amino acids in plasma, which can easily lead to the production of pseudo-neurotransmitters, affect neuronal function, and cause symptoms and signs of various neurological impairments including disturbance of consciousness (12,13). Sharshar et al (14) performed pathological examination on the brain tissue of patients who died of sepsis and found that the incidence of microabscess was high and microabscess may be one of the causes of sepsis-associated encephalopathy.…”
Section: Discussionmentioning
confidence: 99%
“…Hemoperfusion by PMX-F is reported to be safe and effective for sepsis or septic shock and was performed as described previously [6][7][8]13] . PMX is bound by means of its amino group to ␣ -chloracetamidemethyl polystyrene fi bers, and PMX-F consists of a mean 7 mg PMX/1 g fi ber.…”
Section: Methodsmentioning
confidence: 99%
“…The adsorbent column used clinically is a 170-ml polypropylene tube containing 53 g of PMX-F bound covalently to 370 mg PMX. PMX-F therapy was repeated twice with a 24-hour interval as described previously [7,13] . Access to the circulation for direct hemoperfusion with PMX-F was obtained via a double-lumen catheter (Arrow International Inc., Reading, Pa., USA) inserted into the femoral vein by Seldinger's method.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…PMX-F treatment is indicated for use in patients with sepsis or septic shock caused by Gram-negative bacteria. Because of the high affinity of PMX-F for endotoxin, the rationale underlying extracorporeal therapy would be to remove circulating endotoxin by adsorption, thus preventing progression of the biological cascade of sepsis [10,11]. …”
Section: Indicationsmentioning
confidence: 99%